NEW RECORD OF THE EARTHWORM EISENIA FETIDA (SAVIGNY, 1826) FROM KASHMIR VALLEY, JAMMU AND KASHMIR, INDIA - ISHTIYAQ AHMED NAJAR,; ANISA B. KHAN, (The Bioscan, 2011)
The earthworm Eisenia fetida is reported for the first time from the state of Jammu and Kashmir. The original range of the species is supposed from Russia. The species is epigeic and is found in the environments rich in organic matter, with patchy distribution. The life cycle of the earthworm is well documented because of its economic importance as the species is used in waste management.